2021
DOI: 10.1149/1945-7111/ac180e
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Formation of Nd-Fe Alloys in Molten LiF-CaF2-NdF3

Abstract: In the present study, as a fundamental study for recycling Nd from Nd-Fe-B permanent magnet scrap, the electrochemical Nd-alloying behavior of Fe was investigated in a molten LiF-CaF2-NdF3 (0.3 or 0.5 mol%) system at 1123 K. Herein, the equilibrium potential of Nd3+/Nd was determined as 0.18 V (vs Li+/Li) by open-circuit potentiometry using a Mo electrode. Cyclic voltammetry and open-circuit potentiometry were conducted using an Fe electrode, and the results suggested the formation of multiple phases within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…[28][29][30] In the above-mentioned studies, we used solid alloys of RE elements with Ni or Ni-based alloys, as candidate materials for the diaphragm; however, the diffusion of RE elements is expected to be much faster in liquid alloys than in solids. 31 Therefore, we focused on liquid Nd-Fe alloys as candidates for liquid alloy diaphragms and have already reported the results of our investigation of the electrochemical Nd alloying behavior of Fe electrodes in molten LiF-CaF 2 -NdF 3 at 1123 K. 32 In the previous study, we found that liquid Nd-Fe alloys were formed by potentiostatic electrolysis at 0.10 V vs Li + /Li. 32 In this study, the electrochemical formation of Dy-Fe alloys in molten LiF-CaF 2 -DyF 3 at 1123 K was investigated using cyclic voltammetry, open-circuit potentiometry, and potentiostatic electrolysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30] In the above-mentioned studies, we used solid alloys of RE elements with Ni or Ni-based alloys, as candidate materials for the diaphragm; however, the diffusion of RE elements is expected to be much faster in liquid alloys than in solids. 31 Therefore, we focused on liquid Nd-Fe alloys as candidates for liquid alloy diaphragms and have already reported the results of our investigation of the electrochemical Nd alloying behavior of Fe electrodes in molten LiF-CaF 2 -NdF 3 at 1123 K. 32 In the previous study, we found that liquid Nd-Fe alloys were formed by potentiostatic electrolysis at 0.10 V vs Li + /Li. 32 In this study, the electrochemical formation of Dy-Fe alloys in molten LiF-CaF 2 -DyF 3 at 1123 K was investigated using cyclic voltammetry, open-circuit potentiometry, and potentiostatic electrolysis.…”
mentioning
confidence: 99%
“…31 Therefore, we focused on liquid Nd-Fe alloys as candidates for liquid alloy diaphragms and have already reported the results of our investigation of the electrochemical Nd alloying behavior of Fe electrodes in molten LiF-CaF 2 -NdF 3 at 1123 K. 32 In the previous study, we found that liquid Nd-Fe alloys were formed by potentiostatic electrolysis at 0.10 V vs Li + /Li. 32 In this study, the electrochemical formation of Dy-Fe alloys in molten LiF-CaF 2 -DyF 3 at 1123 K was investigated using cyclic voltammetry, open-circuit potentiometry, and potentiostatic electrolysis. Saïla et al investigated the electrochemical behavior of Dy 3+ in LiF-CaF 2 -DyF 3 at 1113-1203 K with the purpose of partitioning and transmutation of long-lived fission products and minor actinides for nuclear waste management.…”
mentioning
confidence: 99%
“…26-30 indicated the reduction of Nd(III) to Nd in two z E-mail: s.kuznetsov@ksc.ru; kuznet@chemy.kolasc.net.ru consecutive steps. There are many studies on the recovery of neodymium with utilization of different cathodes made of Ni, 4,[31][32][33][34][35][36][37][38][39] Cd, 12 Cu, 23,34 Fe, 40 Bi, 41,42 Sn, 42 Al. 12,23,43 The main goal of this study is to determine the standard rate constants of charge transfer (k s ) for the Nd(III)/Nd(II) redox couple and formal standard redox potentials E * Nd(III)/Nd(II) in an equimolar NaCl-KCl mixture.…”
mentioning
confidence: 99%